Legal Regulation of the Operation and Safety Assurance of Hydraulic Structures under Conditions of Sustainable Development - Teleuyev Г.Б.; Bekturganov А.Е.; Yessentemirova А.М. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The article examines issues of legal regulation regarding the operation of hydraulic structures and ensuring their safety within the context of sustainable development in the Republic of Kazakhstan. The authors conduct a comprehensive legal analysis of the current state of hydraulic structures in the country, identifying significant shortcomings in the regulatory framework governing this field. The lack of a clearly defined legal status for hydraulic structures, as well as insufficient development of mechanisms for their management and oversight, contributes to increasing ecological and technological risks. In this regard, the article proposes specific ways to improve regulatory legal acts and enhance their effectiveness based on international experience. Furthermore, particular emphasis is placed on the necessity of adopting specialized legislation aimed at ensuring the safety of hydraulic structures. The research employs methods of normative analysis, comparative legal analysis, and systemic-structural approaches. The results are intended to contribute to the advancement of scientific research in the field of legal regulation of hydraulic structures. The article is aimed at lawyers, environmental specialists, and professionals involved in water resources management. This scientific article was prepared within the framework of implementing Project AP26193915 «Legal Regulation of the Operation and Safety Assurance of Hydraulic Structures under Conditions of Sustainable Development», funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan.